PENGARUH KECERDASAN EMOSIONAL, KARAKTERISTIK PEGAWAI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA MEDAN TIMUR - Yusrani Lubis (Universitas Islam Islam Sumatera Utara, 2020)
The formulation of the problem in this research is how the influence of emotional intelligence on employees performance. How influence of employees characteristic on employees performance. How influence of work motivation on employees performance. How influence of emotional intelligence, employees characteristic and work motivation on employees performance. The purpose of this research is for know influence and analize of emotional intelligence on employees performance. For know influence and analize of employees characteristic on employees performance. For know influence and analize work motivation on employees performance. For know influence and analize emotional intelligence, employees characteristic and work motivation on employees performance. The sample in this research is 86 employees, with data analysis technique used is multiple linear regression analyze. The results of this research explain that emotional intelligence effect has a positive and significant on employee performance. employees characteristic effect has a positive and significant on employee performance. work motivation effect has a positive and significant on employee performance. emotional intelligence, employees characteristic and work motivation effect have a positive and significant on employee performance